Conditional deficiency of m6A methyltransferase Mettl14 in substantia nigra alters dopaminergic neuron function. Issue 17 (21st July 2021) - Teng, Yan; Liu, Zhihao; Chen, Xingmin; Liu, Yanzhuo; Geng, Fan; Le, Weidong; Jiang, Haisong; Yang, Lu
Abstract: N6‐Methyladenosine (m6A) is the most prevalent internal modification in messenger RNAs (mRNAs) of eukaryotes and plays a vital role in post‐transcriptional regulation. Recent studies demonstrated that m6A is essential for the normal function of the central nervous system (CNS), and the deregulation of m6A leads to a series of CNS diseases. However, the functional consequences of m6A deficiency within the dopaminergic neurons of adult brain are elusive. To evaluate the necessity of m6A in dopaminergic neuron functions, we conditionally deleted Mettl14, one of the most important part of m6A methyltransferase complexes, in the substantia nigra (SN) region enriched with dopaminergic neurons. By using rotarod test, pole test, open‐field test and elevated plus maze, we found that the deletion of Mettl14 in the SN region induces impaired motor function and locomotor activity. Further molecular analysis revealed that Mettl14 deletion significantly reduced the total level of m6A in the mRNA isolated from SN region. Tyrosine hydroxylase (TH), an essential enzyme for dopamine synthesis, was also down‐regulated upon Mettl14 deletion, while the activation of microglia and astrocyte was enhanced. Moreover, the expression of three essential transcription factors in the regulation of TH including Nurr1, Pitx3 and En1, with abundant m6A‐binding sites on their RNA 3'‐untranslated regions (UTR), was significantly decreased upon Mettl14 deletion in SN. Our finding first confirmed the significance of m6A in maintaining normal dopaminergic function in the SN of adult mouse.